Potential Phytotherapeutic Approaches for the Treatment of Alzheimer’s Disease: An Overview - Kaushik, Chetna; Yadav, Prarthna (Current Traditional Medicine, 2021)
Alzheimer’s disease is one of the most prevailing age-dependent neurodegenerative diseases and the most common cause of dementia. The pharmacological therapies available for the disease provide only symptomatic relief. Plants are being extensively investigated for Alzheimer’s as they are relatively safer and cheaper. This review summarizes recent findings suggesting anti- Alzheimer potential of the plants along with compounds or mechanisms responsible for their efficacy and their therapeutic targets. The findings of recent studies have revealed that the plants or the compounds isolated from them exhibit mitigative potential in Alzheimer’s disease by targeting amyloid beta, tau protein, cholinergic pathways via various enzymes like beta secretase, gamma secretase, acetylcholinesterase or receptors involved in these pathways. A number of putative compounds revealed from these studies can be investigated further for the mitigation of Alzheimer’s disease.
Keywords: amyloid beta